Energy related services in Kenya: Implications of unbundling the electricity sector on trade in services negotiations - Mburu, Emily Njeri (Research of GSB, 2018)
Electricity is a basic infrastructural service necessary for the achievement of developmental outcomes. The use of electricity, specifically, serves economic as well as social needs. It is universally accepted that electrification enhances quality of life at the household level and stimulates the economy at a broader level. Given its substantial benefits, electrification together with other sources of modern energy such as renewable energy, has been identified as essential for fulfilling the Millennium Development Goals (UNDP, 2005). In most cases, the main challenge in the achievement of these goals is the bundled nature of the electricity supply chain in majority of developing countries. This necessitated the need for policy reforms with the aim of unbundling the sector in Kenya. The literature review sets out to consider the main features of the electricity sector to better understand the legal and regulatory reforms that have taken place in the electricity sector and the impact of the liberalization on rural electrification and the poor in society. It takes note of the changing role of government in the sector with the liberalization and privatization, which has entailed the unbundling of the vertically integrated state-owned utility that has led to the introduction of competition in some segments of the electricity sector value chain such as generation and distribution. In addition, the review considers the classification related issues arising from the reforms that have taken place in the electricity sector and the regulatory imperatives for a competitive electricity services sector. Finally, a review of the reforms in the electricity sector in Kenya is assessed together with the impact of the reforms. Furthermore, the necessary regulatory disciplines instrumental in cross-border trade in electricity services are identified. The rationale of the study focuses mostly on the phenomenological (qualitative) and positivistic (quantitative) types of research. The focus was on identifying, analyzing and reporting patterns (themes) within data to facilitate a clear understanding of the electricity services sector in Kenya. Furthermore, the chapter on methodology presents the research population, sampling strategy, data collection, frame of analysis and a summary of how the data was analysed. Thematic analysis was used to analyse the questions. The findings and discussion sections of the study are focused on the reforms in the electricity services sector in Kenya, the pro-competitive regulations for an effectively liberalized electricity sector, and the resultant electricity-related services. Due to the complexity of the issues in the sector, interviewees preferred to be provided with the questionnaire instead of face-to-face or telephonic interviews. The questionnaire consisted of two sections, namely the respondent's demographics and reforms in the electricity sector in Kenya. The questionnaire targeted key stakeholders in the sector and was sent to eighteen potential respondents, and of these, only fourteen were responsive. The study concludes that reforms in the electricity sector in Kenya have brought about clarity in terms of the services that are embedded in the sector and identified the key regulatory elements necessary to enhance competition in the sector. The new services that have surfaced in Kenya, include geothermal exploration, grid connectivity through KENTRACO, generating electricity from crude oil, and ensuring that more households are connected to the national grid through the rural electrification project.